PENGARUH PEMBERIAN SENYAWA ANTIOKSIDAN SEBELUM SIMPAN TERHADAP UMUR SIMPAN BENIH KAPAS (Gossypium hirsutum L.) - Halimursyadah Halimursyadah (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2008)
The effect of antioxidants as pre-storage treatment to expand the cotton seed storage period Halimursyadah1 dan Endang Murniati2 1Fakultas Pertanian Unsyiah, Nanggroe Aceh Darussalam2Fakultas Pertanian Institut Pertanian Bogor,Bogor ABSTRACTCotton (Gossypium hirsutum L.) seeds ‘Kanesia 8’ were treated with antioxidants to maintain viability and vigor during ageing. Antioxidants which were used are α-tocopherol and extract of red fruit) dissolved in acetone, ascorbic acid dissolved in water also. Seeds were stored at 70-80% relative humidity and 28-29ºC for 12 weeks. Periodically, viability and vigor were determined. Seed viability and vigor were estimated by percentage germination, speed of germination, T50, and Index of vigor. Seeds treated with α-tocopherol 150 ppm showed the highest viability and vigor during the ageing period, while ascorbic acid 300 ppm also retarded the rate of ageing. Treating seeds with red fruits showed the highest of T50. The ability of α-tocopherol, ascorbic acid and red fruit to reduce viability and vigor loss of stored cotton seeds may be due to their ability to inhibit lipid peroxidation.